Physical and chemical properties comparison of natural ester and palm oil used in a distribution transformer - Yannaphol Kittikhuntharadol; Norasage Pattanadech; Sakda Maneerot; Korraya Jongvilaikasem; Kittipod Jariyanurat; Siwakorn Jeenmuang; Patt Udomluksananon; Komin Chumpiboon; Chanin Bunlaksananusorn (My University, 2022)
Because of its low cost and suitable qualities, mineral oil (MO) has been commonly employed in transformers. Alternative liquid insulations with great characteristics have recently been presented. Natural ester (NE) and palm oil (PO) are considered alternative liquid insulations. This paper aims to study the physical and chemical properties of NE and PO which were used in a transformer for 21 months. All of the liquid insulation test specimens were sampled every 3 months. Physical properties of the liquid insulation, i.e., interfacial tension (IFT), viscosity, and particles count, were examined. Chemical properties of the liquid insulation, i.e., moisture content, acidity, corrosive sulfur, and furanic compound (2-FAL), were investigated. IFT, particles count, moisture content, acidity, and 2-FAL test results indicated deterioration of liquid insulations of the used liquid insulation; however, there is no observation change for particles amount and acidity of NE. The other test results were not found significantly change.
Keywords: Mineral oil; Power Transformer Diagnostics and Insulation